2021
DOI: 10.1186/s12903-021-02027-8
|View full text |Cite
|
Sign up to set email alerts
|

Patients with mild cognitive impairment diagnosed at dementia clinic display decreased maximum occlusal force: a cross-sectional study

Abstract: Background Previous research indicates that patients with mild cognitive impairment (MCI) are more likely to have poor oral health and impairments in oral functions, which may be due to few remaining teeth and impaired tongue and lip motor function. However, the oral health of those patients following comprehensive cognitive assessment by a dementia specialist has not been sufficiently investigated. Therefore, this study aimed to clarify the oral function of patients with MCI and the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
9
0
3
Order By: Relevance
“…TP can also be decreased by dysphagia-causing conditions, such as cerebrovascular diseases 3 , neuromuscular dysfunction 4 , Parkinson’s disease 5 , and sarcopenia 6 . In addition, recent evidence suggests that TP may also be decreased in patients with cognitive decline and mild cognitive impairment 7 , 8 . Therefore, a reduction in TP should be considered since it may serve as a valuable index for rehabilitation in dysphagia cases.…”
Section: Introductionmentioning
confidence: 99%
“…TP can also be decreased by dysphagia-causing conditions, such as cerebrovascular diseases 3 , neuromuscular dysfunction 4 , Parkinson’s disease 5 , and sarcopenia 6 . In addition, recent evidence suggests that TP may also be decreased in patients with cognitive decline and mild cognitive impairment 7 , 8 . Therefore, a reduction in TP should be considered since it may serve as a valuable index for rehabilitation in dysphagia cases.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies demonstrated that poorer mastication is associated with lower cognitive function [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ] and is a risk factor for having dementia or mild memory impairment, or for the incidence of dementia [ 48 , 49 , 50 ]. In addition, the physiology of aging leads to atrophy of the masticatory muscles (sarcopenia, hypoactivity of the chewing muscles) [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Highly sedentary humans (≥8 h/day) display reduced hippocampal volumes and increased white matter (WM) hyperintensities [ 3 , 4 ] that are associated with accelerated cognitive, neuropsychiatric and functional decline [ 5 ]. In addition to the changes associated with a sedentary life, it has become clear that oral dysfunction is present in the same individuals and that this group feature is also associated with dementia or mild cognitive decline [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. While it is not clear whether poor oral health predicts dementia, substantial data suggests that oral health declines as cognitive impairment and dementia progresses [ 7 , 12 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the changes associated with a sedentary life, it has become clear that oral dysfunction is present in the same individuals and that this group feature is also associated with dementia or mild cognitive decline [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. While it is not clear whether poor oral health predicts dementia, substantial data suggests that oral health declines as cognitive impairment and dementia progresses [ 7 , 12 , 14 , 15 , 16 ]. Furthermore, it has been demonstrated that masticatory exercise improves cognitive function in older adults [ 17 ] and thus the link between cognitive decline and masticatory dysfunction is now clear [ 8 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation